Observations of a hybrid double-streamer/pseudostreamer in the solar corona - Rachmeler, L.A.; Platten, S.J.; Bethge, C.; Seaton, D.B.; Yeates, A.R. (The Astrophysical Journal, 2014)
We report on the first observation of a single hybrid magnetic structure that contains both a pseudostreamer and a double streamer. This structure was originally observed by the SWAP instrument on board the PROBA2 satellite between 2013 May 5 and 10. It consists of a pair of filament channels near the south pole of the Sun. On the western edge of the structure, the magnetic morphology above the filaments is that of a side-by-side double streamer, with open field between the two channels. On the eastern edge, the magnetic morphology is that of a coronal pseudostreamer without the central open field. We investigated this structure with multiple observations and modeling techniques. We describe the topology and dynamic consequences of such a unified structure.